Penerapan Relaksasi Benson terhadap Kecemasan Pasien Pre Operasi Histerektomi - Enita Sari; M.K. Fitriani Fruitasari; Aniska Indah Fari (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2026)
Hysterectomy is a procedure performed to remove the uterus, either partially or completely. This surgery often causes psychological responses in the form of anxiety. One non-pharmacological therapy that can be used to overcome anxiety is Benson relaxation. The design used in this Final Nursing Scientific Paper is a case study using Benson relaxation intervention. Three respondents participated, and the intervention was carried out for two days preoperatively with three sessions, taking place in the Lukas Charitas Hospital Palembang room. After two days of Benson relaxation, changes in anxiety scores were obtained using the Amsterdam Preoperative Anxiety and Information Scale (APAIS) questionnaire. At the final meeting, Mrs. E's anxiety decreased from 18 to 10, Mrs. H's from 16 to 7, and Mrs. S's from 13 to 7. There was a decrease in anxiety before and after Benson relaxation therapy was administered to all three respondents. The implementation of this EBP is expected to provide additional information regarding the provision of Benson relaxation in preoperative hysterectomy patients.